MANAJEMEN SUMBER DAYA GURU (Studi Kasus Di Madrasah Aliyah Negeri 2 Model Palu) - Suharno Suharno; Titin Fatimah (ISTIQRA, 2015)
This study discusses the implementation of teacher resource management in MAN 2 Model Palu, with the aim to learn more on teacher resource management at the school. By using descriptive qualitative method of this study it can be concluded that 1) Implementation of teacher resources management at MAN 2 Model Palu include: short-term planning is the recruitment through a selection process that uses some selection procedures and establishes the qualifications and criteria for prospective teachers, medium-term planning via Orientation and placement of teacher candidates received a teacher MAN 2 Model Palu, and long-term planning by conducting training and development through the improvement of skills, knowledge and career development of teachers. 2) The driving factor in the implementation of teacher resource management at MAN 2 Model Palu is: the quality of teacher education, teaching conformity with the specifications of science, support the professionalization and MAN management and the government, the decentralization of education, community support for educational institutions. The inhibiting factors are: the limited ability in the management, not the maximum participation of teachers in teaching duties, lack of funds, lack of cooperation with other institutions, there is no clear career for private teachers, well-being, there is no clear vision of the mission of teacher resource management teachers. 3) Efforts made in overcoming obstacles are: clarify the vision and mission of teacher resource management, improve the fungi-teacher resources management functions, network enhancement of cooperation with other institutions, achieving the required qualifications and competencies, build good relationships and extensive peer teacher through organization profession and develop a high work ethic to the constituents